Examining the Learning Styles of Teacher Candidates in Terms of Different Variables - Küçük-demir, Betül; Yılmaz, Demet Deniz (Tamer KUTLUCA, 2023)
Every individual is different from each other, and learning processes can also differ from each other. Therefore, individuals' learning styles may differ from other individual to individual. The purpose of this research is to investigate the learning styles of pre-service teachers in terms of gender, department and class level variables. The survey model, one of the non-experimental research designs, was used in the research. “Kolb Learning Style Inventory” was used as the data collection tool in the research. The sample of the research consists of 328 pre-service teachers who are studying in the 1st, 2nd, 3th and 4th classs of elemantary school teaching (n = 172) and mathematics teaching (n = 156). The data obtained by the Kolb Learning Style Inventory were analyzed using descriptive statistics and chi-square test. As a result of the findings, it was observed that the differentiation of pre-service teachers' learning styles according to their departments, genders and class levels was not statistically significant.
Keywords: Kolb learning style; learning; learning style; pre-service teacher